Two Worlds of Female Labour: Gender Wage Inequality in Western Europe, 1300-1800 - Alexandra M. de Pleijt; Jan Luiten van Zanden (European Historical Economics Society (EHES), 2018)
It is generally acknowledged that the degree to which women participate in labour markets and how they are remunerated are important determinants of female autonomy that may also affect their demographic behaviour. Such links have been discussed in the literature about the "European Marriage Pattern" (EMP). In order to bring about the conditions for female autonomy of the EMP (in which women have a large say in the decision when and with whom they marry), women should have had access to the labour market and have earned a decent wage. This is clearly affected by the gender wage gap and the possibility that women earn their own living and have the option to remain single. But so far no attempt has been made to compare the wages of women across Europe over the long run. In this paper we therefore provide evidence on the wages of unskilled women for seven European countries between 1300 and 1800. Our evidence shows that there were two worlds of female labour. In the South of Europe women earned about 50% of the wage of unskilled male labourers. In the Northern and Western parts of Europe this gap was much smaller during late Medieval Period, but it increased dramatically between about 1500 and 1800.
Keywords: N13; N33; J16; 330; Living standards; labour market; gender inequality; pre-industrial development